Those who select (and those selected). An approximation to the Peronist national deputies for the province of Buenos Aires between 1946 and 1955 (Quinto Sol, 2020)
The article studies the candidate selection process for national deputies by Peronism in four successive elections, developed in 1946, 1948, 1951 and 1954, in the scenario constituted by the province of Buenos Aires. In each case, the ruling group that controlled the selective process, the prevailing formal or informal norms, and the criteria or logic that presided over the process are analyzed. The work is part of current research lines related with the first Peronism, either the one that emphasizes the role of second line leaders and the one that privileges the study of provincial politics. It contributes to the empirical knowledge of Peronist political staff and to the discussion about the organizational dimension of the Peronist movement
Keywords: political parties; peronism; politics; history